Formation of silver chloride nanocrystals as a corrosion product of silver in H2SO4 solution - Picon, C. A. [UNESP]; Fernandes, F. A P; Machado, S. A P; Tremiliosi-Filho, G.; Casteletti, L. C. (The Electrochemical Society, 2012)
The purpose of this study is to characterize the corrosion product on the surface of silver, employing H2SO4 (0.5M) as electrolyte. The electrochemical parameters, Ecor, Icor, V cor and Rp were obtained after analyzing the potentiodynamic polarization curve in which two peaks were observed. The smallest (passive region) is attributed to the Cl- traces from the reference electrode, with micro-cracks. The second peak (in the transpassivation region) corresponds to the polarization curve of silver in H2SO 4 without contaminants. SEM images and EDS analysis reveal images of a surface layer on silver, consisting of structures containing sulfur, oxygen, silver and chloride, as the corrosion product. On this layer silver sulfate crystals were observed, which occurs during the formation of silver chloride nanocrystals with different morphologies, when chloride ions were added to the electrolyte medium. ©The Electrochemical Society.
Keywords: Corrosion products; Electrochemical parameters; Polarization curves; Potentiodynamic polarization curves; Reference electrodes; Silver chlorides; Surface layers; Transpassivation; Chlorine compounds; Corrosion; Electrochemistry; Electrolytes; Nanocrystals; Silver halides; Silver